ATRT-23. SIRT2 cooperates with SMARCB1 to induce a differentiation block in ATRT. (3rd June 2022) - Alimova, Irina; Wang, Dong; Pierce, Angela; Lakshmanachetty, Senthilnath; Prince, Eric; Danis, Etienne; Serkova, Natalie; Madhavan, Krishna; Balakrishnan, Ilango; Yang, Min; Lin, Henning; Foreman, Nicholas; et al.
Abstract: Atypical Teratoid Rhabdoid Tumor is a highly aggressive pediatric brain tumor with poor prognosis driven by loss of the chromatin remodeling factor SMARCB1 that is responsible for determining cellular pluripotency and lineage commitment. The mechanisms by which SMARCB1 deletion results in tumorigenesis remain unclear. We investigated the effect of SIRT2 inhibition in ATRT which was identified as a primary dependency in ATRT. SIRT2 inhibition with shRNA or Thiomyristoyl (TM) decreased ATRT cell growth, inhibited clonogenic potential and leaded to the cell cycle arrest. SIRT2 inhibition effectively suppresses pluripotency-associated genomic programs, significantly changed stem cell frequency, decreased tumor-sphere formation of ATRT cells and attenuated tumor cell self-renewal. In vivo SIRT2 inhibition decreased oncogenic markers and increased accumulation neuronal differentiation markers. Furthermore, SIRT2 induced apoptosis, decreased tumor growth and prolonged survival in orthotopic xenograft models. Single-cell RNA transcriptome analysis of xenoftaft tumors reveals elimination of tumor cells expressing stem cell genes and expansion of tumor cells expressing differentiated genes following TM treatment in ATRT. We demonstrated that SIRT2 inhibition is a molecular vulnerability in SMARCB1-deleted ATRT.